PEMBERDAYAAN KELUARGA DALAM SPIRITUAL-SOCIAL SUPPORT (3S) TERHADAP KESEHATAN FISIK PASIEN KANKER DAN KELUARGA - Qomariah, Siti Nur; Suroso, Heri; Putri, Linta Meyla (Community Development in Health Journal, 2024)
Introduction & Aim: The increasing prevalence of chronic diseases like cancer has made it crucial for society to provide comprehensive and effective care for patients. Physical, psychological, and economic support can significantly impact their health. Research shows that a supportive family can help alleviate symptoms such as depression and physical health issues. To improve the quality of care, comprehensive education and training in management, social environment development, financial support, and personal development should be provided. Spiritual and social environments are essential in preventing negative effects on patient cancer. This community service aims to empower cancer patient families through a spiritual-social support education approach. Method of Activity: This community service uses the PIE (Plan, Implementation, and Evaluation) approach in Surabaya. The activity was conducted over four months, involving surveys and interviews with cancer patients and their families. The implementation of the Spiritual-Social Support (3S) program involved 15 cancer patients and their families, providing education on spiritual definitions, social environment definitions, and social environment implementation. The evaluation of the community's understanding of cancer and physical health. Results: The physical health of cancer patients and their families almost all have normal blood pressure, 90% of which are 12 people. They also have normal body temperature, oxygen saturation, respiratory rate, and pulse. Summative evaluation obtained results that 100% of participants understood the concept of the material that had been taught. Discussion: Increasing comprehensive social and spiritual support, and increasing family knowledge about support resources greatly helps cancer patients undergo therapy and accelerate their recovery.